Improving Students’ Writing Skills Through a Genre-Based Approach Using Canva Application as Media of Twelve Grades Students of SMAN 9 Semarang - Hidayati, Reni (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
Writing is one of the most important skills in English language learning. Written is very difficult to learn even by native speakers of the other three talents because it requires an understanding of various linguistic components and non-linguistic concepts. It often happens in students who are learning English that they still have difficulty in writing good and correct English. It's a problem that sometimes happens to pupils. Therefore, this study aims to improve students’ writing ability through a Genre-based approach using Canva as a media. This study was conducted from July to September of the academic year 2023/2024. The participants of this study are students of the 12th IPS 1. This study used collaborative action research. The technique of collecting data used qualitative and quantitative methods. Quantitative data is obtained from student values consisting of pre-test and post-test, while qualitative data are descriptions of the learning process during the implementation of action. The result of this research found that based on data analysis at the pre-cycle, cycle I, and cycle II stages, it can be concluded that the writing skills of students in the 12th grade IPS 1 High School N 9 Year 2023/2024 can be improved through the application of a Genre-based approach using Canva media as a model and learning medium in writing. This can be seen from the average student scores during pre-cycle, cycle I, and cycle II. The average student score in the pre-test was 45.69%, then increased in the first cycle to 72.87%, and last in the second cycle, the student's average score increased to 8084.03%. So, it can be concluded that the Genre-based approach using Canva media can improve students' writing skills.